Development of a fixed-wing UAS platform for photogrammetric applications - Gutiérrez-Leiva, Edgar (2018)
The present work describes the design process and development of a fixed wing UAS platform for photogrammetry applications, which can be able to perform autonomous missions and collect data for soil analysis through georeferenced images. This work addresses the system level implementation of the UAS platform, as well as its configuration and validation through simple flight missions.